The Impact of Acute Loud Noise on the Behavior of Laboratory Birds - Corbani, Tayanne L.; Martin, Jessica E.; Healy, Susan D. (Frontiers in Veterinary Science, 2021)
Husbandry procedures and facility settings, such as low-frequency fire alarms, can produce noises in a laboratory environment that cause stress to animals used in research. However, most of the data demonstrating harmful effects that have, consequently, led to adaptations to management, have largely come from laboratory rodents with little known of the impacts on avian behaviour and physiology. Here we examined whether exposure to a routine laboratory noise, a low-frequency fire alarm test, induced behavioural changes in laboratory zebra finches (Taeniopygia guttata). Twenty-four breeding pairs of zebra finches were randomly selected and exposed to the low-frequency fire alarm (sounding for 10-20 seconds) or no noise (control) on separate test days. All birds were filmed before and after the alarm sounded and on a control day (without the alarm). The zebra finches decreased their general activity and increased stationary and social behaviours after exposure to the alarm. Brief exposure to a low-frequency alarm disrupted the birds’ behaviour for at least 15 minutes. The induction of this behavioural stress response suggests that low-frequency sound alarms in laboratory facilities have the potential to compromise the welfare of laboratory birds.